2012
DOI: 10.1089/ars.2011.4232
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Heals Indomethacin-Induced Gastric Ulceration by Stimulation of Angiogenesis and Restitution of Collagen FibersviaVEGF and MMP-2 Mediated Signaling

Abstract: We conclude that curcumin remodels gastric tissues by restoring the collagen architecture and accelerating angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The epithelialization period of the treated wounds showed a significant decrease from 23 to 11 days. 33 Similarly, a marked difference was observed in the tensile strength of tissues from the control and experimental incision wounds. A significant increase of 129% in tensile strength was observed on the 8th day in curcumin-treated groups.…”
Section: Role Of Phytochemicals In Skin Regenerationmentioning
confidence: 89%
See 3 more Smart Citations
“…The epithelialization period of the treated wounds showed a significant decrease from 23 to 11 days. 33 Similarly, a marked difference was observed in the tensile strength of tissues from the control and experimental incision wounds. A significant increase of 129% in tensile strength was observed on the 8th day in curcumin-treated groups.…”
Section: Role Of Phytochemicals In Skin Regenerationmentioning
confidence: 89%
“…Furthermore, this study also substantiates that the topical administration of curcumin was found to improve all the phases of wound repair, including collagen synthesis and maturation, wound contraction, and epithelialization. 33 Furthermore, several other investigators also showed that curcumin accelerates the healing of gastric ulcers by reepithelialization, by demonstrating glutathione depletion, lipid peroxidation, and protein oxidation. 28,34,35 Enhanced cell proliferation and an increase in free radicals was also observed in curcumin treatment, which reduces the wound of ulcers.…”
Section: Role Of Phytochemicals In Skin Regenerationmentioning
confidence: 98%
See 2 more Smart Citations
“…(5,6). Curcumin is a polyphenol, derived from the plant Curcuma longa, and has also been investigated as a promising therapy for cancer, infection and dementia (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%